Analisis Perlakuan Akuntansi Zakat Infaq dan Sedekah Berdasarkan PSAK No. 109 di BSI KCP Bondowoso Sudirman - Ahmad Muzayyin; Nurma Yunita (Mazinda : Jurnal Akuntansi, Keuangan, dan Bisnis, 2024)
Bank Syariah Indonesia KCP Bondowoso Sudirman, customers/potential customers from the Bondowoso sub-district are religious in nature and on average the most prioritized and sought after are banks that are based on sharia. The focus of this research is how to treat zakat, infaq and alms accounting at BSI KCP Bondowoso.The purpose of this research is to determine the implementation of accounting treatment based on PSAK No. 109 concerning accounting for zakat infaq and alms at the Indonesian Sharia Bank Institution KCP Bondowoso Sudirman. This type of research is field research using qualitative methods with a descriptive approach. Data obtained through the process of observation, semi-structured interviews and documentation. Then the data obtained is processed through three stages, namely, data reduction, data presentation, and drawing conclusions. Data validity was carried out by testing data credibility and theory triangulation.The research results show that the recognition, measurement, presentation and disclosure of zakat, infaq and shadokah transactions at Bank Syariah Indonesia is in accordance with financial accounting standard statement number 109.